Exogenous Estradiol: Productive and Reproductive Performance and Physiological Profile of Japanese Quail Hens - Elnaga, Samar A.; Abd-Elhady, Ahmed M. (International Journal of Poultry Science, 2009)
Seventy two, 3 weeks old female quails were distributed among 2 treatments to study the effect of estradiol administration, on their productive and reproductive performance. Birds of the first group were intramuscularly injected at 3 weeks of age daily with 100 μg E2 /bird/day for 14 consecutive days. Birds of the second group served as control. Birds injected with E2 from 3-5 weeks of age had a significantly higher body weight at sexual maturity and matured significantly earlier compared to control. Egg number, egg weight and egg mass had significantly increased due to E2 injection. Ovaries and oviducts relative weight, oviducts length, magnum length were none significantly increased while, shell gland length increased significantly by 17% due to estradiol injection. Serum calcium increased significantly due to E2 injections. This was also accompanied with significant increase in Tibia weight (22%) and calcium content (10%) in compare to the untreated females. Estradiol injections resulted in a significant increase in egg shell percent and calcium content. Data indicated a stimulated pancreatic activity, as plasma glucose decreased while liver glycogen increased due to the treatment. Plasma total lipids, cholesterol and triglycerides levels were increased by 25, 20 and 22%, respectively. Similar trend was observed with liver lipids content, which was reflected on yolk lipids content. There were no significant differences observed on egg quality due to estradiol treatment. Serum transaminases (GOT and GPT) activities increased with E2 treatment while T3 decreased. It can be concluded that treating immature Japanese quails daily (for 2 weeks) with E2 can enhance their reproductive and productive functions without affecting their physiological profile or their egg quality.